Big Data Analytics and Knowledge Discovery : 17th International Conference, DaWaK 2015, Valencia, Spain, September 1-4, 2015, Proceedings - Madria, Sanjay; Hara, Takahiro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 17th International Conference on Data Warehousing and Knowledge Discovery, DaWaK 2015, held in Valencia, Spain, September 2015. The 31 revised full papers presented were carefully reviewed and selected from 90 submissions. The papers are organized in topical sections similarity measure and clustering; data mining; social computing; heterogeneos networks and data; data warehouses; stream processing; applications of big data analysis; and big data.
Keywords: Database management; Data mining; Information systems; Information storage and retrieva; Database Management; Data Mining and Knowledge Discovery; Computer Appl. in Administrative Data Processing; Information Storage and Retrieval; Information Systems Applications (incl. Internet).